Malignant tumors of major salivary glands - Rajer, Mirjana; Strojan, Primož (Onkologija : Slovenian Journal of Oncology, 2009)
Malignant tumors of major salivary glands are a rare and heterogeneous group of diseases. On average, 8 people in Slovenia are diagnosed with this disease every year. In the article, anatomy, epidemiological and etiological characteristics as well as diagnostic procedures and treatment principles applied in these tumors, are presented. Furthermore, we reviewed modes and results of therapy of malignant tumors of major salivary glands as conducted at the Institute of Oncology Ljubljana during 1980-2004. They were compared with results of similar institutions from elsewhere in the world.